Exchange Street after its widening, October 8, 1929 - Boston Globe (Tufts Archival Research Center, 2005)
Elevated view of Exchange Street after its widening. Automobiles, trucks, wagons and motorcycles fill the street, which is lined with street lamps. An empty lot filled with debris is visible along the left side of the street. Pedestrians are included in the photograph. 7 9/16 x 6 7/16, 7 15/16 x 6 7/16 overall Photographs